Kristendommen er ikke nogen "stor fortælling" - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 1987)
H.J.L. Jensen: “Christianity is not a ‘great narrative’. A structural note on a typology of universal narratives” and P. Aa. Brandt: “Narrative and linguistic event. Comments on H.J.L. Jensen’s structural note”. Jean-François Lyotard has recently focused on the demise of the “great narratives”. But what is the nature of these narratives? Jensen’s note establishes an inventory of 8 types of “universal narratives” based on three axes: A) fall vs. erection, B) mythology vs. eschatology, and C) human vs. inhuman. The “great narrative” can be characterized as a “human-erective-eschatology” whereas the core of the Christian narrative is “inhuman-erective-mythology”. The 8 types can as well be coordinated or embedded in different ways. In his comment, Brandt reformulates Jensen’s conclusions into a semiotic, generative theory of narrative sequence which involves three levels: 1) Jensen’s (A) is related to the actantial level, 2) his (B) to the discursive level, and 3) his (C) to the enunciative level. The 8 types can be rearranged in the light of the theory of speech-acts in which the addressed is attributed a lack (or deficiency?) either in the present or the future. This provides two main types of “narrative linguistic events”: the promise, which moves from the dysphoric present to the euphoric future; and the threat, which moves from the euphoric present to the dysphoric future. These linguistic events are embedded in narrative sequences. Religion as preaching is a combination of promise and threat which cannot avoid “narrativising” the addressed in the small, but tendentious, as well as in the great narratives. Hans J. Lundager Jensen og Per Aage Brandt